Biochar-based slow-release fertilizer and preparation method thereof

By adopting a multi-layer structural design in biochar slow-release fertilizer, combining graphene quantum dot modified biochar, composite microbial bacteria agent and magnetic nanoparticles, the problem of inadequate microbial activity protection and dynamic release fertilizer requirements in the existing technology is solved, efficient fertilizer utilization and crop adaptability is achieved, and soil repair and stress resistance functions are provided, and sustainable solutions are provided for modern agriculture.

CN119797996AInactive Publication Date: 2025-04-11ZIYUYUAN (SHANDONG) ECOLOGICAL TECH CO LTD

Patent Information

Application Number
CN202510286022.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-12
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing biochar sustained-release fertilizers fail to take into account the needs of microbial activity protection and dynamic release fertilizers, resulting in low sustained-release efficiency.

Method used

It adopts a multi-layer structure design, including core, carrier layer, biological layer and protective layer. The core is composed of nitrogen fertilizer, potassium fertilizer and phosphorus fertilizer. The carrier layer uses graphene quantum dot modified biochar powder. The biological layer is added with composite microbial bacteria agent and magnetic Fe3O4@humic acid nanoparticles. The protective layer uses polylactic acid-polycaprolactone block copolymer and dynamic covalent crosslinking agent.

Benefits of technology

It significantly improves fertilizer utilization efficiency and crop adaptability, with a yield increase of 23-27%, and has soil restoration and stress resistance functions, providing innovative solutions for sustainable agriculture.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a biochar-based slow-release fertilizer and a preparation method thereof, and relates to the technical field of fertilizer production, the biochar-based slow-release fertilizer comprises a core, a carrier layer, a biological layer and a protective layer, the core is composed of macroelements, microelements and a nitrification inhibitor; the carrier layer comprises graphene quantum dot modified charcoal, chitosan, glycerol and cyclodextrin grafted starch; the biological layer is prepared from magnetic Fe3O4 and humic acid nanoparticles, alginic acid oligosaccharide and diatomite; the protective layer comprises a polylactic acid-polycaprolactone block copolymer, acetone, calcium lignosulphonate, a dynamic covalent cross-linking agent gelatin, nano cellulose and an anti-blocking agent. Therefore, by adopting the polylactic acid-polycaprolactone (PLA-PCL)-based segmented copolymer and the dynamic covalent network cross-linking agent, the self-repairing property is endowed. The slow-release fertilizer provided by the invention realizes precise regulation and control of the fertilizer efficiency release rate through a multi-level synergistic effect, has the functions of soil remediation and stress resistance, and significantly improves the utilization efficiency of the fertilizer and the crop adaptability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fertilizer production, and in particular to a biochar-based slow-release fertilizer and a preparation method thereof. Background Art

[0002] Biochar has high carbon content and porosity, which can improve soil texture, increase soil fertility, improve soil physical and chemical properties and microbial activity, thereby increasing crop yield and quality and enhancing crop resistance. In addition, biochar can also be used as a slow-release carrier for fertilizers, improving fertilizer utilization efficiency and reducing environmental pollution.

[0003] For example, the Chinese patent with the publication number "CN117510276A" discloses a "biochar-based slow-release fertilizer and its preparation method", and its technical scheme is: "It includes a slow-release material and agricultural fertilizer in a weight ratio of 2:8; wherein the slow-release material includes equal weights of attapulgite and biochar, and the attapulgite includes a first attapulgite pretreated with thermal modification, a second attapulgite pretreated with acid modification, and a third attapulgite pretreated with thermal modification and acid modification in sequence; the biochar used includes a first biochar pretreated with acid modification, a second biochar pretreated with phosphorus modification, and a third biochar pretreated with acid modification and phosphorus modification in sequence. The present invention obtains a new type of biochar-based slow-release fertilizer with good slow-release performance and high loading capacity by compounding the slow-release material of the attapulgite-biochar composite with agricultural fertilizer, which can improve the utilization rate of fertilizers, increase soil nutrients, and thereby achieve the beneficial effects of shortening the growth and development period of crops and increasing crop yields."

[0004] In the existing technology, biochar slow-release fertilizer has low slow-release efficiency due to its rough process. Although the above scheme improves the adsorption capacity through modification, it fails to take into account the protection of microbial activity and the dynamic release of fertilizer requirements. Summary of the invention

[0005] In view of the above defects, the purpose of the present invention is to provide a biochar-based slow-release fertilizer and a preparation method thereof, aiming to solve the problem that biochar slow-release fertilizers in the prior art fail to take into account both the protection of microbial activity and the dynamic release of fertilizer.

[0006] In order to solve the above technical problems, the technical solution of the present invention is: The biochar-based slow-release fertilizer comprises a core, a carrier layer, a biological layer and a protective layer arranged in sequence from the inside to the outside. The core is composed of 40-65 parts of macroelements, 10-35 parts of trace elements and 5-20 parts of nitrification inhibitors by weight; the carrier layer is composed of 30-42 parts of graphene quantum dot-modified biochar powder, 18-28 parts of chitosan, 6-12 parts of glycerol and 10-16 parts of cyclodextrin grafted starch; the biological layer is composed of 3 The invention comprises 5-40 parts of composite microbial agents, 12-20 parts of magnetic Fe3O4@humic acid nanoparticles, 10-15 parts of alginate oligosaccharides and 8-12 parts of diatomaceous earth; the protective layer comprises 18-25 parts of polylactic acid-polycaprolactone block copolymer, 25-28 parts of acetone, 15-22 parts of calcium lignin sulfonate, 5-10 parts of dynamic covalent crosslinking agent, 3-5 parts of gelatin, 6-10 parts of nanocellulose and 8-10 parts of anti-caking agent.

[0007] Wherein, the macroelements are composed of nitrogen fertilizer, potash fertilizer and phosphate fertilizer, wherein the nitrogen fertilizer is urea, the potash fertilizer is potassium sulfate and the phosphate fertilizer is calcium hydrogen phosphate; by weight, the nitrogen fertilizer is 25-45 parts, the phosphate fertilizer is 20-35 parts and the potash fertilizer is 12-20 parts.

[0008] Wherein, the trace elements are composed of 10-20 parts of zinc chloride, 10-20 parts of magnesium sulfate, 10-20 parts of ferrous sulfate, 10-15 parts of calcium nitrate, 4-5 parts of manganese oxide and 15-20 parts of wood ash, calculated by mass.

[0009] Wherein, the nitrification inhibitor is composed of 85-90 parts of DMPP, 5-8 parts of triphenyl thiophosphate and 5-7 parts of cyclodextrin-embedded inositol peptide.

[0010] Wherein, the anti-caking agent is composed of 20-30 parts of diatomaceous earth, 10-20 parts of sodium aluminosilicate, 10-15 parts of silicon dioxide and 30-35 parts of deionized water in parts by mass.

[0011] Among them, a preparation method based on biochar slow-release fertilizer includes the following steps: Step 1, preparing a core; Place urea, potassium sulfate and calcium hydrogen phosphate in a melting tank and heat to 160-180°C to melt; add trace elements and nitrification inhibitors crushed to 100 mesh, stir at 300 rpm, and mix for 30 minutes; use a twin-screw extruder granulator to granulate, with a core particle size of 0.8-2.5 mm, a drying temperature of 80°C, and a drying time of 1.5-3h; Step 2, spraying the carrier layer; Graphene quantum dot modified biochar powder, chitosan, glycerol and cyclodextrin grafted starch are ultrasonically dispersed to form a colloidal solution, and a porous carrier layer is formed on the surface of the core by electrospraying at a spraying temperature of 50-60°C and a spraying pressure of 5-8MPa; Step 3, spraying the biological layer; Alginate oligosaccharide and diatomite deionized water are mixed into a slurry, and the composite microbial agent and magnetic Fe3O4@humic acid nanoparticles are assembled on the surface of the carrier layer through a magnetic field, and then the slurry is sprayed. After spraying, it is low-temperature dried. The spraying temperature is 25-35°C, the spraying pressure is 2-3MPa, and the low-temperature drying temperature is 20-25°C; Step 4: spraying a protective layer; The polylactic acid-polycaprolactone block copolymer is dissolved in acetone, mixed with a dynamic covalent crosslinking agent solution in a volume ratio of 3:1, and sprayed onto the biolayer in an atomized manner. The spraying pressure is 4-5 MPa and the spraying temperature is 25-35°C to form a self-repairing film layer with a thickness of 20-30 μm. Finally, an anti-caking agent is sprayed and the finished fertilizer is obtained after low-temperature drying at a temperature of 20-25°C.

[0012] In step 2, the preparation method of graphene quantum dot modified biochar powder is: 2 / g of biochar is immersed in a graphene quantum dot dispersion liquid with a concentration of 0.8-1.5 mg / ml, ultrasonically treated for 1-2 hours, and dried to obtain modified biochar.

[0013] Wherein, in step 2, the working voltage of the electrospray is 17-19 kV, the nozzle diameter is 0.3-0.4 mm, the carrier gas flow rate is 0.35-0.6 L / min, and the porosity of the porous carrier layer is formed to be ≥60%.

[0014] In step three, FeCl2·4H2O and FeCl3·6H2O are dissolved in deionized water at a molar ratio of 1:2, and then humic acid is added to obtain magnetic Fe3O4@humic acid nanoparticles with a particle size of 50-100 nm; ammonia water is added dropwise at 78-82°C to a pH of 9.5-10, and the mixture is washed and dried after magnetic separation, and then an alternating magnetic field with a frequency of 50 Hz and an intensity of 0.5 T is used to uniformly distribute the magnetic Fe3O4@humic acid nanoparticles on the surface of the carrier layer; the solid content of the slurry is 12-16%, and the saturation magnetization intensity is ≥45emu / g.

[0015] The preparation method of the dynamic covalent crosslinker is as follows: benzaldehyde-terminated PEG with a molecular weight of 2000Da is mixed with hydrazide chitosan with a substitution degree of ≥80% in a molar ratio of 1:1.5, and then a buffer solution with a pH of 4.8-5.2 is added to obtain a dynamic covalent crosslinker with a reversible acylhydrazone bond after the reaction.

[0016] After adopting the above technical solution, the beneficial effects of the present invention are: First, the slow-release fertilizer consists of a core, a carrier layer, a biological layer and a protective layer, which greatly slows down the release rate of the fertilizer effect. Second, the carrier layer innovatively introduces graphene quantum dots to modify biochar, which significantly enhances the adsorption of the carrier layer, and the carrier layer contains nutrients that can provide nutrients for the early incubation and reproduction of biological bacteria. Third, the biological layer adds new salt-alkali tolerant strains and magnetic nano-humic acid complexes to enhance the synergistic effect of microbial activity and nutrient slow release. Fourth, the protective layer adopts a block copolymer based on polylactic acid-polycaprolactone (PLA-PCL) and a dynamic covalent network crosslinker to give it self-healing properties. Through multi-level synergy, the present invention not only significantly improves fertilizer utilization efficiency and crop adaptability (yield increase rate 23-27%), but also has soil remediation (organic matter increase 18-21%) and stress resistance (pH of saline-alkali land reduced by 0.6-0.9), providing an innovative solution for the sustainable development of modern agriculture. DETAILED DESCRIPTION

[0017] It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention.

[0018] Example: The biochar-based slow-release fertilizer comprises a core, a carrier layer, a biological layer and a protective layer arranged in sequence from the inside to the outside. The core is composed of 40-65 parts of macroelements, 10-35 parts of trace elements, and 5-20 parts of nitrification inhibitors by weight; the carrier layer is composed of 30-42 parts of graphene quantum dot modified biochar powder, 18-28 parts of chitosan, 6-12 parts of glycerol, and 10-16 parts of cyclodextrin grafted starch; the biological layer is composed of 35-40 parts of composite microelement powder, 10-28 parts of chitosan, 6-12 parts of glycerol, and 10-16 parts of cyclodextrin grafted starch; the biological layer is composed of 35-40 parts of composite microelement powder, 10-28 parts of chitosan, 6-12 parts of glycerol, and 10-2 ... The invention discloses a biological bacterial agent, 12-20 parts of magnetic Fe3O4@humic acid nanoparticles, 10-15 parts of alginate oligosaccharides, and 8-12 parts of diatomaceous earth; the protective layer is composed of 18-25 parts of polylactic acid-polycaprolactone (PLA-PCL) block copolymer, 25-28 parts of acetone, 15-22 parts of calcium lignin sulfonate, 5-10 parts of dynamic covalent cross-linking agent (based on acylhydrazone bond), 3-5 parts of gelatin, 6-10 parts of nanocellulose, and 8-10 parts of anti-caking agent.

[0019] The core particle size in this solution is 0.8-2.5 mm, and the composite microbial agent includes a variety of salt-alkali tolerant bacteria. Halobacillus nitroreducens, Bacillus subtilis, phosphate-solubilizing bacteria, nitrogen-fixing bacteria, etc., where the total amount of bacteria in the biolayer is ≥ 4.5×10 8 CFU / g.

[0020] The role of the carrier layer is to isolate the biolayer from the core, preventing dormant bacteria in the biolayer from being "burned to death" after waking up due to the high concentration of core nutrients. The Fe3O4@humic acid nanoparticles in the biolayer are distributed in a directional manner through the magnetic field, enhancing the efficiency of local microbial colonization, while the slow release of humic acid promotes root development. The role of the protective layer is to reduce the damage to the biolayer by external forces. At the same time, the dynamic covalent network based on acylhydrazone bonds can autonomously repair microcracks under wet and hot conditions and extend the slow release period.

[0021] In this scheme, the macro-elements are composed of nitrogen fertilizer, potash fertilizer and phosphate fertilizer. The nitrogen fertilizer is urea, the potash fertilizer is potassium sulfate and the phosphate fertilizer is calcium hydrogen phosphate. By weight, the nitrogen fertilizer is 25-45 parts, the phosphate fertilizer is 20-35 parts and the potash fertilizer is 12-20 parts.

[0022] Calculated by mass, the trace elements are composed of 10-20 parts of zinc chloride, 10-20 parts of magnesium sulfate, 10-20 parts of ferrous sulfate, 10-15 parts of calcium nitrate, 4-5 parts of manganese oxide and 15-20 parts of wood ash.

[0023] The nitrification inhibitor is composed of 85-90 parts of DMPP, 5-8 parts of triphenyl thiophosphate (TPPT) and 5-7 parts of cyclodextrin-embedded inositol peptide.

[0024] In terms of weight, the anti-caking agent is composed of 20-30 parts of diatomaceous earth, 10-20 parts of sodium aluminosilicate, 10-15 parts of silicon dioxide and 30-35 parts of deionized water.

[0025] A method for preparing a biochar-based slow-release fertilizer comprises the following steps: Step 1, preparing a core; Urea, potassium sulfate and calcium hydrogen phosphate were placed in a melting tank and heated to 160-180°C to melt; trace elements and nitrification inhibitors crushed to 100 mesh were added, the stirring rate was 300 rpm, and the mixing time was 30 minutes; a twin-screw extruder granulator (model: SLG-60, Jiangsu Hengli Machinery) was used for granulation, the core particle size was 0.8-2.5 mm, the drying temperature was 80°C, and the drying time was 1.5-3h; Step 2, spraying the carrier layer; Graphene quantum dot modified biochar powder, chitosan, glycerol and cyclodextrin grafted starch are ultrasonically dispersed to form a colloidal solution, and a porous carrier layer is formed on the surface of the core by electrospraying at a spraying temperature of 50-60°C and a spraying pressure of 5-8MPa; Step 3, spraying the biological layer; Alginate oligosaccharide, diatomaceous earth and deionized water are mixed into a slurry, and the composite microbial agent and magnetic Fe3O4@humic acid nanoparticles are assembled on the surface of the carrier layer through a magnetic field, and then the slurry is sprayed. After spraying, it is low-temperature dried. The spraying temperature is 25-35°C, the spraying pressure is 2-3MPa, and the low-temperature drying temperature is 20-25°C. Step 4: spraying a protective layer; The polylactic acid-polycaprolactone block copolymer is dissolved in acetone, mixed with a dynamic covalent crosslinking agent solution in a volume ratio of 3:1, and sprayed onto the biolayer in an atomized manner. The spraying pressure is 4-5 MPa and the spraying temperature is 25-35°C to form a self-repairing film layer with a thickness of 20-30 μm. Finally, an anti-caking agent is sprayed and the finished fertilizer is obtained after low-temperature drying at a temperature of 20-25°C.

[0026] In step 2, the preparation method of graphene quantum dot modified biochar powder is: 2 / g of biochar is immersed in a graphene quantum dot dispersion liquid with a concentration of 0.8-1.5 mg / ml, ultrasonically treated for 1-2 hours, and dried to obtain modified biochar.

[0027] In step 2, the working voltage of the electrospray is 17-19 kV, the nozzle diameter is 0.3-0.4 mm, the carrier gas flow rate is 0.35-0.6 L / min, and the porosity of the porous carrier layer is formed to be ≥60%.

[0028] In step three, FeCl2·4H2O and FeCl3·6H2O are dissolved in deionized water in a molar ratio of 1:2, and then humic acid (20% w / w) is added to obtain magnetic Fe3O4@humic acid nanoparticles with a particle size of 50-100 nm; ammonia water is added dropwise at 78-82°C to a pH of 9.5-10, and the mixture is washed and dried after magnetic separation, and then an alternating magnetic field with a frequency of 50 Hz and an intensity of 0.5 T is used to evenly distribute the magnetic Fe3O4@humic acid nanoparticles on the surface of the carrier layer; the solid content of the slurry is 12-16%, and the saturation magnetization intensity is ≥45 emu / g.

[0029] The preparation method of the dynamic covalent crosslinker is as follows: benzaldehyde-terminated PEG with a molecular weight of 2000Da is mixed with hydrazide chitosan with a substitution degree of ≥80% in a molar ratio of 1:1.5, and then a buffer solution with a pH of 4.8-5.2 is added to obtain a dynamic covalent crosslinker with a reversible acylhydrazone bond after reaction.

[0030] Embodiment 1: This embodiment adopts the preparation method of biochar-based slow-release fertilizer recorded in the above scheme to prepare finished fertilizer, and its specific contents are as follows: The core is composed of 40 parts of macroelements, 10 parts of trace elements, and 5 parts of nitrification inhibitors; the carrier layer is composed of 30 parts of graphene quantum dot modified biochar powder, 18 parts of chitosan, 6 parts of glycerol, and 10 parts of cyclodextrin grafted starch; the biological layer is composed of 35 parts of composite microbial agents, 12 parts of magnetic Fe3O4@humic acid nanoparticles, 10 parts of alginate oligosaccharides, and 8 parts of diatomaceous earth; the protective layer is composed of 18 parts of polylactic acid-polycaprolactone block copolymer, 25 parts of acetone, 15 parts of calcium lignin sulfonate, 5 parts of dynamic covalent cross-linking agents, 3 parts of gelatin, 6 parts of nanocellulose and 8 parts of anti-caking agents.

[0031] The nitrogen fertilizer is 25 parts, the phosphorus fertilizer is 20 parts, and the potassium fertilizer is 12 parts.

[0032] The trace elements are composed of 10 parts of zinc chloride, 10 parts of magnesium sulfate, 10 parts of ferrous sulfate, 10 parts of calcium nitrate, 4 parts of manganese oxide and 15 parts of wood ash.

[0033] The nitrification inhibitor is composed of 85 parts of DMPP, 5 parts of triphenyl thiophosphate and 5 parts of cyclodextrin-embedded inositol peptide.

[0034] The anti-caking agent consists of 20 parts of diatomaceous earth, 10 parts of sodium aluminosilicate, 10 parts of silicon dioxide and 30 parts of deionized water.

[0035] In step 1, urea, potassium sulfate and calcium hydrogen phosphate are placed in a melting tank and heated to 160° C. to melt; the core particle size is 0.8 mm, the drying temperature is 80° C., and the drying time is 1.5 h; In step 2, a porous carrier layer is formed on the surface of the core by electrospraying, with a spraying temperature of 50° C. and a spraying pressure of 5 MPa; In step 3, the spraying temperature is 25°C, the spraying pressure is 2MPa, and the low-temperature drying temperature is 20°C; In step 4, the spraying pressure is 4 MPa and the spraying temperature is 25°C to form a self-repairing film layer with a thickness of 20 μm. Finally, the anti-caking agent is sprayed. After low-temperature drying, the finished fertilizer is obtained. The low-temperature drying temperature is 20°C.

[0036] In step 2, the operating voltage of the electrospray was 17 kV, the nozzle diameter was 0.3 mm, and the carrier gas flow rate was 0.35 L / min.

[0037] In step 2, the preparation method of graphene quantum dot modified biochar powder is: 2 / g of biochar was immersed in a graphene quantum dot dispersion liquid with a concentration of 0.8 mg / ml, ultrasonically treated for 1 hour, and dried to obtain modified biochar.

[0038] In step three, FeCl2·4H2O and FeCl3·6H2O are dissolved in deionized water at a molar ratio of 1:2, and then humic acid is added to obtain magnetic Fe3O4@humic acid nanoparticles with a particle size of 50 nm; ammonia water is added dropwise at 78°C to a pH of 9.5, and the mixture is washed and dried after magnetic separation. Subsequently, an alternating magnetic field with a frequency of 50 Hz and an intensity of 0.5 T is used to evenly distribute the magnetic Fe3O4@humic acid nanoparticles on the surface of the carrier layer; the solid content of the slurry is 12%, and the saturation magnetization intensity is ≥45 emu / g.

[0039] The preparation method of the dynamic covalent crosslinker is as follows: benzaldehyde-terminated PEG with a molecular weight of 2000Da is mixed with hydrazide chitosan with a substitution degree of ≥80% in a molar ratio of 1:1.5, and then a buffer solution with a pH of 4.8 is added to obtain a dynamic covalent crosslinker with a reversible acylhydrazone bond after reaction.

[0040] Embodiment 2: The difference between this embodiment and embodiment 1 is that: The core is composed of 50 parts of macroelements, 20 parts of trace elements, and 15 parts of nitrification inhibitors; the carrier layer is composed of 32 parts of graphene quantum dot modified biochar powder, 20 parts of chitosan, 8 parts of glycerol, and 12 parts of cyclodextrin grafted starch; the biological layer is composed of 36 parts of composite microbial agents, 14 parts of magnetic Fe3O4@humic acid nanoparticles, 12 parts of alginate oligosaccharides, and 10 parts of diatomaceous earth; the protective layer is composed of 20 parts of polylactic acid-polycaprolactone block copolymer, 25.5 parts of acetone, 16 parts of calcium lignin sulfonate, 6 parts of dynamic covalent cross-linking agent, 3.5 parts of gelatin, 8 parts of nanocellulose and 8.5 parts of anti-caking agent.

[0041] The nitrogen fertilizer is 28 parts, the phosphorus fertilizer is 22 parts, and the potassium fertilizer is 14 parts.

[0042] The trace elements are composed of 12 parts of zinc chloride, 12 parts of magnesium sulfate, 12 parts of ferrous sulfate, 11 parts of calcium nitrate, 4.5 parts of manganese oxide and 17 parts of wood ash.

[0043] The nitrification inhibitor is composed of 86 parts of DMPP, 5.5 parts of triphenyl thiophosphate and 5.5 parts of cyclodextrin-embedded inositol peptide.

[0044] The anti-caking agent consists of 22 parts of diatomaceous earth, 12 parts of sodium aluminosilicate, 11 parts of silicon dioxide and 31 parts of deionized water.

[0045] In step 1, urea, potassium sulfate and calcium hydrogen phosphate are placed in a melting tank and heated to 170°C for melting; the core particle size is 1 mm, the drying temperature is 80°C, and the drying time is 2 hours; In step 2, a porous carrier layer is formed on the surface of the core by electrospraying, with a spraying temperature of 55° C. and a spraying pressure of 6 MPa; In step 3, the spraying temperature is 28°C, the spraying pressure is 2.5MPa, and the low-temperature drying temperature is 22°C; In step four, the spraying pressure is 4.5 MPa and the spraying temperature is 28°C, forming a self-repairing film layer with a thickness of 24 μm. Finally, the anti-caking agent is sprayed, and the finished fertilizer is obtained after low-temperature drying is completed. The low-temperature drying temperature is 22°C.

[0046] In step 2, the electrospray operating voltage was 18 kV, the nozzle diameter was 0.4 mm, and the carrier gas flow rate was 0.4 L / min.

[0047] In step 2, the preparation method of graphene quantum dot modified biochar powder is: 2 / g of biochar was immersed in a graphene quantum dot dispersion liquid with a concentration of 1 mg / ml, ultrasonically treated for 1.2 hours, and dried to obtain modified biochar.

[0048] In step three, FeCl2·4H2O and FeCl3·6H2O are dissolved in deionized water at a molar ratio of 1:2, and then humic acid is added to obtain magnetic Fe3O4@humic acid nanoparticles with a particle size of 60 nm; ammonia water is added dropwise at 80°C to a pH of 9.7, and the mixture is washed and dried after magnetic separation. Subsequently, an alternating magnetic field with a frequency of 50 Hz and an intensity of 0.5 T is used to evenly distribute the magnetic Fe3O4@humic acid nanoparticles on the surface of the carrier layer; the solid content of the slurry is 13%, and the saturation magnetization intensity is ≥45 emu / g.

[0049] The preparation method of the dynamic covalent crosslinker is as follows: benzaldehyde-terminated PEG with a molecular weight of 2000Da is mixed with hydrazide chitosan with a substitution degree of ≥80% in a molar ratio of 1:1.5, and then a buffer solution with a pH of 5 is added to obtain a dynamic covalent crosslinker with a reversible acylhydrazone bond after reaction.

[0050] Embodiment 3: The difference between this embodiment and embodiment 1 is that: The core is composed of 60 parts of macroelements, 30 parts of trace elements, and 18 parts of nitrification inhibitors; the carrier layer is composed of 38 parts of graphene quantum dot modified biochar powder, 26 parts of chitosan, 10 parts of glycerol, and 14 parts of cyclodextrin grafted starch; the biological layer is composed of 38 parts of composite microbial agents, 18 parts of magnetic Fe3O4@humic acid nanoparticles, 14 parts of alginate oligosaccharides, and 11 parts of diatomaceous earth; the protective layer is composed of 22 parts of polylactic acid-polycaprolactone block copolymer, 27 parts of acetone, 20 parts of calcium lignin sulfonate, 8 parts of dynamic covalent cross-linking agent, 4 parts of gelatin, 9 parts of nanocellulose and 9 parts of anti-caking agent.

[0051] The nitrogen fertilizer is 40 parts, the phosphorus fertilizer is 30 parts, and the potash fertilizer is 18 parts.

[0052] The trace elements are composed of 18 parts of zinc chloride, 18 parts of magnesium sulfate, 18 parts of ferrous sulfate, 14 parts of calcium nitrate, 4.8 parts of manganese oxide and 19 parts of wood ash.

[0053] The nitrification inhibitor is composed of 88 parts of DMPP, 7 parts of triphenyl thiophosphate and 6 parts of cyclodextrin-embedded inositol peptide.

[0054] The anti-caking agent consists of 28 parts of diatomaceous earth, 18 parts of sodium aluminosilicate, 14 parts of silicon dioxide and 34 parts of deionized water.

[0055] In step 1, urea, potassium sulfate and calcium hydrogen phosphate are placed in a melting tank and heated to 175°C for melting; the core particle size is 2 mm, the drying temperature is 80°C, and the drying time is 2.5 hours; In step 2, a porous carrier layer is formed on the surface of the core by electrospraying, with a spraying temperature of 58° C. and a spraying pressure of 7 MPa; In step 3, the spraying temperature is 30°C, the spraying pressure is 2.8MPa, and the low-temperature drying temperature is 24°C; In step 4, the spraying pressure is 4.8 MPa and the spraying temperature is 30°C to form a self-repairing film layer with a thickness of 28 μm. Finally, the anti-caking agent is sprayed. After low-temperature drying, the finished fertilizer is obtained. The low-temperature drying temperature is 24°C.

[0056] In step 2, the operating voltage of the electrospray was 18.5 kV, the nozzle diameter was 0.4 mm, and the carrier gas flow rate was 0.5 L / min.

[0057] In step 2, the preparation method of graphene quantum dot modified biochar powder is: 2 / g of biochar was immersed in a graphene quantum dot dispersion liquid with a concentration of 1.3 mg / ml, ultrasonically treated for 1.8 hours, and dried to obtain modified biochar.

[0058] In step three, FeCl2·4H2O and FeCl3·6H2O are dissolved in deionized water at a molar ratio of 1:2, and then humic acid is added to obtain magnetic Fe3O4@humic acid nanoparticles with a particle size of 60 nm; ammonia water is added dropwise at 81°C to a pH of 9.8, and the mixture is washed and dried after magnetic separation. Subsequently, an alternating magnetic field with a frequency of 50 Hz and an intensity of 0.5 T is used to evenly distribute the magnetic Fe3O4@humic acid nanoparticles on the surface of the carrier layer; the solid content of the slurry is 14%, and the saturation magnetization intensity is ≥45 emu / g.

[0059] The preparation method of the dynamic covalent crosslinker is as follows: benzaldehyde-terminated PEG with a molecular weight of 2000Da is mixed with hydrazide chitosan with a substitution degree of ≥80% in a molar ratio of 1:1.5, and then a buffer solution with a pH of 5.1 is added to obtain a dynamic covalent crosslinker with a reversible acylhydrazone bond after reaction.

[0060] Embodiment 4: The difference between this embodiment and embodiment 1 is that: The core is composed of 65 parts of macroelements, 35 parts of trace elements, and 20 parts of nitrification inhibitors; the carrier layer is composed of 42 parts of graphene quantum dot modified biochar powder, 28 parts of chitosan, 12 parts of glycerol, and 16 parts of cyclodextrin grafted starch; the biological layer is composed of 40 parts of composite microbial agents, 20 parts of magnetic Fe3O4@humic acid nanoparticles, 15 parts of alginate oligosaccharides, and 12 parts of diatomaceous earth; the protective layer is composed of 25 parts of polylactic acid-polycaprolactone block copolymer, 28 parts of acetone, 22 parts of calcium lignin sulfonate, 10 parts of dynamic covalent cross-linking agent, 5 parts of gelatin, 10 parts of nanocellulose and 10 parts of anti-caking agent.

[0061] The nitrogen fertilizer is 45 parts, the phosphorus fertilizer is 35 parts, and the potash fertilizer is 20 parts.

[0062] The trace elements are composed of 20 parts of zinc chloride, 20 parts of magnesium sulfate, 20 parts of ferrous sulfate, 15 parts of calcium nitrate, 5 parts of manganese oxide and 20 parts of wood ash.

[0063] The nitrification inhibitor is composed of 90 parts of DMPP, 8 parts of triphenyl thiophosphate and 7 parts of cyclodextrin-embedded inositol peptide.

[0064] The anti-caking agent consists of 30 parts of diatomaceous earth, 20 parts of sodium aluminosilicate, 15 parts of silicon dioxide and 35 parts of deionized water.

[0065] In step 1, urea, potassium sulfate and calcium hydrogen phosphate are placed in a melting tank and heated to 180°C for melting; the core particle size is 2.5 mm, the drying temperature is 80°C, and the drying time is 3 hours; In step 2, a porous carrier layer is formed on the surface of the core by electrospraying, with a spraying temperature of 60° C. and a spraying pressure of 8 MPa; In step 3, the spraying temperature is 35°C, the spraying pressure is 3MPa, and the low-temperature drying temperature is 25°C; In step four, the spraying pressure is 5 MPa and the spraying temperature is 35°C to form a self-repairing film layer with a thickness of 30 μm. Finally, the anti-caking agent is sprayed. After low-temperature drying, the finished fertilizer is obtained. The low-temperature drying temperature is 25°C.

[0066] In step 2, the operating voltage of the electrospray was 19 kV, the nozzle diameter was 0.4 mm, and the carrier gas flow rate was 0.6 L / min.

[0067] In step 2, the preparation method of graphene quantum dot modified biochar powder is: 2 / g of biochar was immersed in a graphene quantum dot dispersion liquid with a concentration of 1.5 mg / ml, ultrasonically treated for 2 hours, and dried to obtain modified biochar.

[0068] In step three, FeCl2·4H2O and FeCl3·6H2O are dissolved in deionized water at a molar ratio of 1:2, and then humic acid is added to obtain magnetic Fe3O4@humic acid nanoparticles with a particle size of 60 nm; ammonia water is added dropwise at 82°C to a pH of 10, and the mixture is washed and dried after magnetic separation. Subsequently, an alternating magnetic field with a frequency of 50 Hz and an intensity of 0.5 T is used to evenly distribute the magnetic Fe3O4@humic acid nanoparticles on the surface of the carrier layer; the solid content of the slurry is 16%, and the saturation magnetization intensity is ≥45 emu / g.

[0069] The preparation method of the dynamic covalent crosslinker is as follows: benzaldehyde-terminated PEG with a molecular weight of 2000Da is mixed with hydrazide chitosan with a substitution degree of ≥80% in a molar ratio of 1:1.5, and then a buffer solution with a pH of 5.2 is added to obtain a dynamic covalent crosslinker with a reversible acylhydrazone bond after reaction.

[0070] Comparative Example 1: The difference between this comparative example and Example 1 is that: The core is composed of 30 parts of macroelements, 5 parts of trace elements, and 3 parts of nitrification inhibitors; the carrier layer is composed of 20 parts of graphene quantum dot modified biochar powder, 14 parts of chitosan, 3 parts of glycerol, and 2 parts of cyclodextrin grafted starch; the biological layer is composed of 20 parts of composite microbial agents, 8 parts of magnetic Fe3O4@humic acid nanoparticles, 5 parts of alginate oligosaccharides, and 4 parts of diatomaceous earth; the protective layer is composed of 10 parts of polylactic acid-polycaprolactone block copolymer, 20 parts of acetone, 10 parts of calcium lignin sulfonate, 2 parts of dynamic covalent cross-linking agents, 1 part of gelatin, 2 parts of nanocellulose and 2 parts of anti-caking agents.

[0071] The nitrogen fertilizer is 10 parts, the phosphorus fertilizer is 12 parts, and the potassium fertilizer is 10 parts.

[0072] The trace elements are composed of 5 parts of zinc chloride, 5 parts of magnesium sulfate, 5 parts of ferrous sulfate, 5 parts of calcium nitrate, 2 parts of manganese oxide and 5 parts of wood ash.

[0073] The nitrification inhibitor is composed of 70 parts of DMPP, 2 parts of triphenyl thiophosphate and 2 parts of cyclodextrin-embedded inositol peptide.

[0074] The anti-caking agent consists of 10 parts of diatomaceous earth, 5 parts of sodium aluminosilicate, 5 parts of silicon dioxide and 20 parts of deionized water.

[0075] Comparative Example 2: The difference between this comparative example and Example 1 is that: The core is composed of 70 parts of macroelements, 40 parts of trace elements, and 25 parts of nitrification inhibitors; the carrier layer is composed of 45 parts of graphene quantum dot modified biochar powder, 30 parts of chitosan, 15 parts of glycerol, and 20 parts of cyclodextrin grafted starch; the biological layer is composed of 45 parts of composite microbial agents, 22 parts of magnetic Fe3O4@humic acid nanoparticles, 20 parts of alginate oligosaccharides, and 15 parts of diatomaceous earth; the protective layer is composed of 30 parts of polylactic acid-polycaprolactone block copolymer, 30 parts of acetone, 25 parts of calcium lignin sulfonate, 15 parts of dynamic covalent cross-linking agent, 6 parts of gelatin, 15 parts of nanocellulose and 15 parts of anti-caking agent.

[0076] The nitrogen fertilizer is 50 parts, the phosphorus fertilizer is 40 parts, and the potassium fertilizer is 25 parts.

[0077] The trace elements are composed of 25 parts of zinc chloride, 25 parts of magnesium sulfate, 25 parts of ferrous sulfate, 25 parts of calcium nitrate, 10 parts of manganese oxide and 25 parts of wood ash.

[0078] The nitrification inhibitor is composed of 92 parts of DMPP, 10 parts of triphenyl thiophosphate and 8 parts of cyclodextrin-embedded inositol peptide.

[0079] The anti-caking agent consists of 40 parts of diatomaceous earth, 25 parts of sodium aluminosilicate, 25 parts of silicon dioxide and 40 parts of deionized water.

[0080] The finished fertilizer products in Example 1 to Example 4 and Comparative Example 1 to Comparative Example 2 were selected respectively, and the finished fertilizer products were placed in the soil of the same environment. The physical properties thereof are shown in Table 1.

[0081] Table 1 Comparison of core components and physical properties of the embodiments and comparative examples

[0082] Comparative Example 3: The difference between this comparative example and Example 1 is that no polylactic acid-polycaprolactone (PLA-PCL) block copolymer is added to the protective layer.

[0083] Through experimental observation, we found that the self-repair efficiency of the protective layer is close to 0.

[0084] Comparative Example 4: The difference between this comparative example and Example 1 is that no graphene quantum dot-modified biochar powder is added to the carrier layer.

[0085] Through experimental observation, we found that the porosity of the carrier layer (%) was 18, which is significantly lower than the normal values ​​of Examples 1 to 4. At the same time, the survival rate of microorganisms also decreased to 1.5×10 8 CFU / g.

[0086] The finished fertilizers in Examples 1 to 4 and Comparative Examples 1 to 2 were selected respectively, and the finished fertilizers were placed in the soil of the same environment. The fertilizer release rate and the soil improvement effect (measured for 240 days) are shown in Table 2: Table 2 Fertilizer release rate and soil improvement effect (240-day test)

[0087] The finished fertilizer products in Example 1 and Comparative Example 1 were selected respectively, and the finished fertilizer products were placed in the soil of the same environment. The fertilizer functions thereof are shown in Table 3: Table 3 Fertilizer function verification

[0088] It can be seen from Table 1 that Examples 1-4 achieve a synergistic slow-release effect with the carrier layer and the biological layer by rationally proportioning nitrogen fertilizer (25%-45%), phosphorus fertilizer (20%-35%), and potassium fertilizer (12%-20%) to meet the growth needs of crops. Its compressive strength is 16.2-19.5 N, the porosity of the carrier layer is 62%-70%, and the microbial survival rate is 4.8×10 8 -5.7×10 8 CFU / g, the self-repair efficiency was 92%-96%, showing good mechanical properties, slow-release effect and bacterial activity. In contrast, the comparative example 1 had low nutrient dosage (nitrogen 20%, phosphorus 10%, potassium 8%), uneven fertilizer release (cumulative release rate 58%), low porosity (50%), and low microbial survival rate (2.1×10 8 CFU / g, the performance is poor. Although the comparative example 2 has high compressive strength (20.1 N) and high microbial survival rate (5.9×10 8 CFU / g) and high self-repair efficiency (97%), but excessive addition of nutrients causes particle cracking, increases costs by 30%, and excessively thick film layers affect nutrient release, resulting in poor practicality.

[0089] It can be concluded from Table 2 that: Examples 1-4: The fertilizer release rate is between 60-63%, the sustained release effect is stable and meets the design requirements, reflecting the precise controlled release ability of the multilayer structure. Comparative Example 1 (low-profile version): The release rate is 58%, which is significantly lower than that of the example, indicating that reducing the amount of core material will lead to a decrease in sustained release efficiency. Comparative Example 2 (high-profile version): The release rate is 60.1%, which is close to the example, but the cost increases by 30%, and the cost performance is insufficient.

[0090] It can be seen from Table 3 that the experimental results show that Example 1 uses magnetic field directional distribution technology to achieve uniform distribution of magnetic particles with a coverage rate of ≥95%, and can complete dynamic self-repair of cracks in only 2 hours under hot and humid conditions; while Comparative Example 1 has significantly insufficient performance due to the random distribution of the magnetic field (coverage rate ≤60%) and lack of self-repair function. This comparison verifies the necessity and superiority of the technical innovation of the present invention in improving material functionality and reliability through the synergistic effect of directional magnetic field control and self-repair mechanism.

[0091] In summary, the material selection range provided in this scheme is optimal, and the advantages of this scheme are: First, the slow-release fertilizer is composed of a core, a carrier layer, a biological layer and a protective layer, which greatly slows down the release rate of fertilizer effect. Second, the carrier layer innovatively introduces graphene quantum dots to modify biochar, which significantly enhances the adsorption of the carrier layer, and the carrier layer contains nutrients, which can provide nutrients for the early incubation and reproduction of biological bacteria. Third, the biolayer adds new salt-alkali tolerant strains and magnetic nano-humic acid complexes to enhance the synergistic effect of microbial activity and nutrient slow release. Fourth, the protective layer adopts a block copolymer based on polylactic acid-polycaprolactone (PLA-PCL) and a dynamic covalent network crosslinker to give it self-repairing properties. Through multi-level synergy, the present invention not only significantly improves fertilizer utilization efficiency and crop adaptability (yield increase rate 23-27%), but also has soil remediation (organic matter increase 18-21%) and stress resistance (pH of saline-alkali land reduced by 0.6-0.9), providing an innovative solution for the sustainable development of modern agriculture.

[0092] The present invention is not limited to the above-mentioned specific implementation modes. Various changes made by ordinary technicians in this field based on the above-mentioned concepts without creative work are all within the protection scope of the present invention.

Claims

1. A slow-release fertilizer based on biochar, characterized in that: The invention comprises a core, a carrier layer, a biological layer and a protective layer which are arranged in sequence from the inside to the outside. In terms of weight, the core consists of 40-65 parts of macroelements, 10-35 parts of trace elements and 5-20 parts of nitrification inhibitors; the carrier layer consists of 30-42 parts of graphene quantum dot modified biochar powder, 18-28 parts of chitosan, 6-12 parts of glycerol and 10-16 parts of cyclodextrin grafted starch; the biological layer consists of 35-40 parts of composite microbial agents, 12-20 parts of magnetic Fe3O4@humic acid nanoparticles, 10-15 parts of alginate oligosaccharides and 8-12 parts of diatomaceous earth; and the protective layer consists of 18-25 parts of polylactic acid-polycaprolactone block copolymer, 25-28 parts of acetone, 15-22 parts of calcium lignin sulfonate, 5-10 parts of dynamic covalent crosslinking agents, 3-5 parts of gelatin, 6-10 parts of nanocellulose and 8-10 parts of anti-caking agents.

2. The biochar-based slow-release fertilizer according to claim 1, characterized in that: The macroelements are composed of nitrogen fertilizer, potash fertilizer and phosphate fertilizer, wherein the nitrogen fertilizer is urea, the potash fertilizer is potassium sulfate and the phosphate fertilizer is calcium hydrogen phosphate; by weight, the nitrogen fertilizer is 25-45 parts, the phosphate fertilizer is 20-35 parts and the potash fertilizer is 12-20 parts.

3. The biochar-based slow-release fertilizer according to claim 1, characterized in that: Calculated by mass, the trace elements are composed of 10-20 parts of zinc chloride, 10-20 parts of magnesium sulfate, 10-20 parts of ferrous sulfate, 10-15 parts of calcium nitrate, 4-5 parts of manganese oxide and 15-20 parts of wood ash.

4. The biochar-based slow-release fertilizer according to claim 1, characterized in that: The nitrification inhibitor is composed of 85-90 parts of DMPP, 5-8 parts of triphenyl thiophosphate and 5-7 parts of cyclodextrin-embedded inositol peptide.

5. The biochar-based slow-release fertilizer according to claim 1, characterized in that: In terms of weight, the anti-caking agent is composed of 20-30 parts of diatomaceous earth, 10-20 parts of sodium aluminosilicate, 10-15 parts of silicon dioxide and 30-35 parts of deionized water.

6. A method for preparing a biochar-based slow-release fertilizer according to claim 1, characterized in that: The steps include: Step 1, preparing a core; Place urea, potassium sulfate and calcium hydrogen phosphate in a melting tank and heat to 160-180°C to melt; add trace elements and nitrification inhibitors crushed to 100 mesh, stir at 300 rpm, and mix for 30 minutes; use a twin-screw extruder granulator to granulate, with a core particle size of 0.8-2.5 mm, a drying temperature of 80°C, and a drying time of 1.5-3h; Step 2, spraying the carrier layer; Graphene quantum dot modified biochar powder, chitosan, glycerol and cyclodextrin grafted starch are ultrasonically dispersed to form a colloidal solution, and a porous carrier layer is formed on the surface of the core by electrospraying at a spraying temperature of 50-60°C and a spraying pressure of 5-8MPa; Step 3, spraying the biological layer; Alginate oligosaccharide and diatomite deionized water are mixed into a slurry, and the composite microbial agent and magnetic Fe3O4@humic acid nanoparticles are assembled on the surface of the carrier layer through a magnetic field, and then the slurry is sprayed. After spraying, it is low-temperature dried. The spraying temperature is 25-35°C, the spraying pressure is 2-3MPa, and the low-temperature drying temperature is 20-25°C; Step 4: spraying a protective layer; The polylactic acid-polycaprolactone block copolymer is dissolved in acetone, mixed with a dynamic covalent crosslinking agent solution in a volume ratio of 3:1, and sprayed onto the biolayer in an atomized manner. The spraying pressure is 4-5 MPa and the spraying temperature is 25-35°C to form a self-repairing film layer with a thickness of 20-30 μm. Finally, an anti-caking agent is sprayed and the finished fertilizer is obtained after low-temperature drying at a temperature of 20-25°C.

7. The method for preparing the biochar-based slow-release fertilizer according to claim 6, characterized in that: In step 2, the preparation method of graphene quantum dot modified biochar powder is: 2 / g of biochar is immersed in a graphene quantum dot dispersion liquid with a concentration of 0.8-1.5 mg / ml, ultrasonically treated for 1-2 hours, and dried to obtain modified biochar.

8. The method for preparing the biochar-based slow-release fertilizer according to claim 6, characterized in that: In step 2, the working voltage of the electrospray is 17-19 kV, the nozzle diameter is 0.3-0.4 mm, the carrier gas flow rate is 0.35-0.6 L / min, and the porosity of the porous carrier layer is formed to be ≥60%.

9. The method for preparing a biochar-based slow-release fertilizer according to claim 6, characterized in that: In step three, FeCl2·4H2O and FeCl3·6H2O are dissolved in deionized water in a molar ratio of 1:2, and then humic acid is added to obtain magnetic Fe3O4@humic acid nanoparticles with a particle size of 50-100 nm; ammonia water is added dropwise at 78-82°C to a pH of 9.5-10, and the mixture is washed and dried after magnetic separation. Subsequently, an alternating magnetic field with a frequency of 50 Hz and an intensity of 0.5 T is used to evenly distribute the magnetic Fe3O4@humic acid nanoparticles on the surface of the carrier layer; the solid content of the slurry is 12-16%, and the saturation magnetization intensity is ≥45 emu / g.

10. The method for preparing the biochar-based slow-release fertilizer according to claim 6, characterized in that: The preparation method of the dynamic covalent crosslinker is as follows: benzaldehyde-terminated PEG with a molecular weight of 2000Da is mixed with hydrazide chitosan with a substitution degree of ≥80% in a molar ratio of 1:1.5, and then a buffer solution with a pH of 4.8-5.2 is added to obtain a dynamic covalent crosslinker with a reversible acylhydrazone bond after reaction.

Citation Information

Patent Citations

  • Potassium humate selenium-rich compound fertilizer and preparation method thereof

    CN110437014A

  • Seaweed extract coated fertilizer for better crops and soil health

    CN112930330A

  • Large-particle slow-release fertilizer as well as preparation method and application thereof

    CN115677418A

  • Novel humic acid water-soluble fertilizer and preparation method thereof

    CN116606179A

  • Self-repairing hydrogel with acylhydrazone bond and disulfide bond and preparation method thereof

    CN117264238A

Cited By

  • Intelligent controlled-release core-shell alginate soil conditioner and preparation method thereof

    CN120172793A

  • Intelligent controlled-release core-shell alginate soil conditioner and preparation method thereof

    CN120172793B

  • Composite material as well as preparation method and application thereof

    CN121950323A

  • Chitosan / diatomite coated charcoal-based slow release fertilizer as well as preparation method and application thereof

    CN122059746A